PASTORAL KONSELING SEBAGAI SARANA PREVENTIF PERCERAIAN - Brek, Yohan; Lombogia, Randy A. A. P. (Institut Agama Kristen Negeri Manado, 2021)
Divorce between marriage couple, every year has increased, therefore, how the task of the church in maintaining and caring for congregations or christians families to stay to keep the chastity and keep the sacred vows of marriage. The purpose of this study to describe the actions of Pastoral Counseling, and also to be a means of Preventing Divorce in the Christian Evangelical Church in Sangihe Talaud, and the results of the research that show how Pastoral Counseling is an important tool carried out by GMIST in an effort to prevent divorce in the congregation. Hopefully this research can add insight into knowledge about how to Prevent Divorce through Pastoral Counseling, also may be able to help every servant of God to know the right way to shepherd every family that is on the verge of divorce.